Children of Parents With a Mental Illness—Stigma Questionnaire: Development and Piloting - Dobener, Lisa-Marie; Stracke, Markus; Viehl, Kathrin; Christiansen, Hanna (Frontiers in Psychiatry, 2022)
Children of parents with a mental illness are a particularly vulnerable group as they have a high risk to develop a mental disorder themselves and those are associated with high stigma. Moreover, just like primary recipients of stigma, they are affected by the social taboo surrounding mental illness: they do not receive enough information, are often left alone with their problems, and are thus considered “invisible children”. In previous research, family stigma has only been assessed through general questionnaires for all family members. What has not yet been adequately investigated is how stigma difficulties affect the children of parents with mental illness in particular. To address these limitations, we developed the Children of Parents with Mental Illness-Stigma-Questionnaire (COPMI-SQ), a self-report instrument for young people aged 12–19 years, designed to assess young people's stigma experiences in daily life. Based on a systematic review preceding the questionnaire, we identified relevant stigma dimensions for children of parents with a mental illness that resulted in 93 items that according to theory were assumed to load on four different scales: experienced stigma, anticipated stigma, self-stigma, and structural discrimination. An expert discussion, and a comprehensibility analysis with the target group followed. In this paper, we report on the development process and initial pilot data (N = 32) on the psychometric properties of the COPMI-SQ. Item analyses via an item difficulty index, discriminatory power, as well as internal consistency analysis resulted in a revised instrument reduced to 67 items. We observed very high internal consistencies (between α = 0.868 and α = 0.975) for the subscales. The approach taken to develop the COPMI-SQ followed scientifically accepted principles by ensuring different construction phases and is considered a solid basis for further reliability and validity studies. The study is ongoing and undergoing a further validation investigation; dimensionality and factor structure will also be examined.